Structural-Electromagnetic-Thermal Coupling Technology for Active Phased Array Antenna - Pengying Xu; Yan Wang; Xiaoxian Xu; Longyang Wang; Zhihai Wang; Kunpeng Yu; Wenzhi Wu; Meng Wang; Guojun Leng; Dongming Ge; Xiaofei Ma; Congsi Wang (International Journal of Antennas and Propagation)
Active phased array antenna (APAA) is a representative of complex electronic equipment, and it plays significant roles in scenarios such as battlefield situation perception, aviation guidance, and communication. It has become the core equipment in land, navigation, and aeronautical applications. With the continuous improvement of technical changes and military requirements, the working frequency band, pointing accuracy, gain, and low sidelobe level of APAA increase, and the multi-disciplinary design contradiction between antenna electrical performance and structure and temperature becomes increasingly prominent. As a result, the electrical performance of APAA in service is prone to be affected by the external complex environments. The structural-electromagnetic-thermal (SET) coupling problem has become a key problem restricting the development of APAA. This paper has summarized the structural features and environmental loads of advanced APAA on different platforms and provided design basis and principle for antenna designer. And then the SET coupling theory of APAA has been introduced, which can be applied in both the design and manufacturing stage, as well as the performance control technology in service environment of APAA. This theory helps to analyze the impact of environmental factors, such as antenna structure deformation, radome high-temperature ablation, and feed errors, on the antenna's performance. For 128 × 768 spaceborne array antenna, in the range of 25∼85°C, the gain of antenna decreases with the increase of operating temperature and decreases by 0.015 dB with each increase of 1°C. The key design parameters in the fields of antenna manufacturing accuracy, efficient heat dissipation, and lightweight design are also analysed; for 32 × 32 rectangular planar phased array antenna, the gain of antenna decreases by 2.715 dB when the random error of installation position in x, y, and z direction reaches 1/10 of the wavelength. In addition, condition monitoring, displacement field reconstruction, and electrical performance compensation of APAA have also been touched to help engineers maintain and guarantee the antenna performance throughout its life cycle. Finally, the future research direction of SET technology of APAA has been discussed, and SET technology is extended to more fields such as antenna parameter uncertainty, high-frequency circuit electronics manufacturing, and electronic equipment performance guarantee.